Need for turbo-charging: with focus on producer gas-fuelled internal combustion engines - a review. (2017) - Kulkarni, Vivek V.; Anil, T.R.; Rajan, N.K.S.
The vital need for the reduction of harmful environmental impact during energy production necessitates research for efficient, economically feasible energy developing techniques. Hence much greater emphasis is being placed on reducing the fuel consumption of engines due to global move to reduce CO2 emissions. One of them is the use of gaseous fuel, namely producer gas (PG), as full supplement fuel in internal combustion engines. The earlier studies on use of PG in engines for power generation have reported a de-rating in their delivered peak power. Since PG can be obtained from various biomass gasification sources, the literature also suggests a varying de-rating of 20-40% on different spark ignited engines used by different researchers. To overcome this difficulty, turbo-charging is known to be a better option to recover the power loss from a given engine size. This paper emphasises the need of turbocharger for producer gas-fuelled spark ignited internal combustion engine.